Fighter in velvet gloves : Alaska civil rights hero Elizabeth Peratrovich - Boochever, Annie (University of Alaska Press, 2019)
"'No Natives or Dogs Allowed" blared the storefront sign at the young Tlingit Indian girl. The sting of those words would stay with Elizabeth Peratrovich all her life. Years later, a seasoned fighter for equality, she would deliver her own eloquent message. One that helped change Alaska and the nation forever. Tensions could not have been higher in Gallery B of the Alaska Territorial Senate. Alaska Natives and non-Natives pressed shoulder to shoulder or stood teetering on chairs to peer over the avalanche of heads that flowed into the hallway. They had come to hear debate on the first anti-discrimination bill in America, almost 20 years before passage of the United States Civil Rights Act. One speaker remained. Now thirty-three years old, Elizabeth Peratrovich placed her knitting next to her young daughter and rose. Dignified and confident in white velvet gloves, stylish green dress and matching hat, she made her way slowly down the crowded aisle. The audience strained forward, drawn by her calm but powerful presence. She turned to face the assembled legislators. Fighter in Velvet Gloves traces Elizabeth's life, from birth and adoption to leadership in a battle for civil rights now celebrated annually throughout Alaska on Elizabeth Peratrovich Day. Author Annie Boochever grew up in Juneau, Alaska. She and her family knew many of the Alaskans, including political leaders, who played key roles in Elizabeth's life and in the battle for Alaska Native people's equality. Written in collaboration with Elizabeth's eldest son, Roy Peratrovich Jr., Fighter in Velvet Gloves brings to life for readers, age ten through young adult, the story of an inspirational Alaskan and American hero"--Provided by publisher.